Analyzing The Role Of Health Media In Promoting Community Response To Saudi Red Crescent Initiatives During Crises (The Review of Diabetic Studies, 2025)
This study aimed to analyze the role of health media in promoting the community’s response to the Saudi Red Crescent Authority’s initiatives during crises, through a questionnaire consisting of 15 items designed on a three-point Likert scale (disagree, neutral, agree). The study population consisted of individuals who followed various media outlets during health crises, while the sample consisted of (200) individuals who were randomly selected.  The study utilized the descriptive analytical approach as it was the most suitable for the nature of the subject. and the data were analyzed using descriptive statistical methods (frequencies, percentages, means, and standard deviation). The results showed an overall mean of responses of 1.97, indicating a neutral but leaning towards a positive attitude towards the role of health media. The tables showed that items related to providing positive volunteer models and spreading awareness about Red Crescent initiatives came at the top of the evaluations, while items related to conveying humanitarian messages and the accuracy of information received relatively lower averages. The reliability analysis results (Cronbach's alpha = 0.006) also showed that the instrument needs further revision to improve internal consistency between items. The study concludes that health media has a tangible impact on raising awareness and community engagement with Red Crescent initiatives, but this role still needs more organization and effectiveness through improving the accuracy of messages and the speed of disseminating information during crises.